STUDENTS’ PERCEPTION ON THE TEACHER’S NON-VERBAL COMMUNICATION IN TEACHING ENGLISH AT SMAN 14 BOMBANA - Marianti, Marianti; Sale, Firdaus; Tasrim, Isnada Waris (Universitas Halu Oleo, 2020)
Many teachers understand that the use of nonverbal communication in teaching process is a good way to support the students’ understanding. By this effort, students may reach good comprehension through their belief for every act of teaching and learning process. This belief can be scripted to picture their perception. The students’ perception is all the students’ mental images and feeling which happen during their activities in the school. This means that any activities where the students gain information, the perception exist there. In this thesis, the students’ perception determines the function of the teacher’s nonverbal communication. The aim of this research was to investigate the students’ perception on the teacher’s nonverbal communication in teaching English at SMAN 14 Bombana. The research used a qualitative design with the subject of the study was class X and XI IPA. The total numbers of these two classes were 47. The researcher used classroom observation sheet and semi-structure interview as the instrument of the research, the interview which was the questions were formulated but, in the field, the interviewer might modify the format or questions during the interview process. This process took place to both of the students and the teacher. After collecting data, the data was analyzed descriptively. The result showed that the students agreed that the use of nonverbal communication in the teaching and learning process works. All of the expected meaning behind the nonverbal communication could be understood by the students well. The entire teacher’s nonverbal communication where the researcher focused namely gestures, eye contact, and tone of voice functioned well. Most of the students agreed that the teacher’s nonverbal communication made them motivated to learn, focused their attention, and made them eagerly to speak, and sometimes, it made the students proud